Hukum dan Kebijakan Keamanan Siber: Tantangan Regulasi Perangkat IoT - Anwar, Yatama Zahra; Sanmorino, Ahmad (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
The Internet of Things (IoT) has impacted many sectors such as industry, health, and households, with the ability to connect physical objects to the internet network. However, this development is accompanied by major challenges related to cybersecurity, including the risk of data intrusion, cyberattacks, and privacy violations. One fundamental problem is the lack of uniform security standards, which causes various manufacturers' implementation differences. In addition, many IoT devices are not designed with security as a priority, making them vulnerable to attacks. Other challenges include the lack of user awareness of the importance of data security and the limitations of cross-country regulations in monitoring and enforcing IoT security laws. This article explores the challenges in cybersecurity regulation on IoT and offers policies that support increased security. The main contribution of this article is to provide insight into the problems of IoT regulation and provide practical solutions to reduce cyber risks on IoT devices. These solutions are expected to be a guide for policymakers in formulating dynamic regulations, under the development of IoT technology.